Private Health Sector in India-Ready and Willing, Yet Underutilized in the Covid-19 Pandemic: A Cross-Sectional Study - Davalbhakta, Samira; Sharma, Supriya; Gupta, Shefali; Agarwal, Vishwesh; Pandey, Gaurav; Misra, Durga Prasanna; Naik, Bijaya Nanda; Goel, Ashish; Gupta, Latika; Agarwal, Vikas (Frontiers in Public Health, 2020)
Background: The private medical sector is a resource that must be estimated for efficient inclusion into public healthcare during pandemics. Methods: A survey was conducted among private healthcare workers to ascertain their views on the potential resources that can be accessed from the private sector and methods to do the same. Results: There were 213 respondents, 80% of them being doctors. Nearly half (47.4%) felt that the contribution from the private medical sector has been suboptimal. Areas suggested for improved contributions by the private sector related to patient care (71.8%) and provision of equipment (62.4%), with fewer expectations (39.9%) on the research front. Another area of deemed support was maintaining continuity of care for non-COVID patients using virtual consultation services (77.4%), tele-consultation being the preferred option (60%). 58.2% felt that the Government had not involved the private sector adequately; and 45.1% felt they should be part of policy-making. Conclusion: A streamlined pathway to facilitate the private sector to join hands with the public sector for a national cause is the need of the hour. Through our study, we have identified gaps in the current contribution by the private sector and identified areas in which they could contribute, by their own admission.